THE INFLUENCE OF NON-PERFORMING LOANS (NPL), LOAN OF DEPOSIT RATIO (LDR), OPERATING COST OF OPERATING INCOME (BOPO), QUALITY OF EARNING ASSETS (KAP) AND CAPITAL ADEQUACY REQUIREMENT (CAR). EARNING ASSETS (KAP) AND MINIMUM CAPITAL ADEQUACY (KPMM) ON RETURN - Agiastia, Dhita; Prasetyo, Agung Slamet; Setyowati, Hasanah; Ambarwati, Lilik; Mutahir, Anwar; Mahsun, Mohamad; Subkhan, Muhammad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study aims to analyze how financial ratios in Bank Perekonomin Rakyat, namely Non-Performing Loan (NPL), Loan of Deposit Ratio (LDR), Operating Costs Operating Income (BOPO), Earning Asset Quality (KAP) and the influence of Minimum Capital Adequacy (CAR) affect the level of profitability projected from the Return of Asset (ROA) ratio. The sample in this study used purposive sampling method, namely the People's Economic Bank in Bantul Regency which is registered with the Financial Services Authority for the period 2020-2023. The secondary data used are publication reports obtained from accessing the Financial Services Authority website (www.ojk.go.id) which are then recorded into SPSS. The data analysis method uses a classic assumption test which includes normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The analysis tool technique is descriptive analysis and statistical analysis. The results showed that CAR has a positive and significant effect on ROA, NPL and BOPO have a negative and significant effect on ROA while LDR and KAP have an insignificant effect on ROA.